A DFT study on Dichloro{(E)-4-dimethylamino-N′-[(pyridin-2 yl)methylidene-κN]benzohydrazide-κO}M2+ (M=Zn, Cu, Ni and Co) complexes: Effect of the metal over association energy and complex geometry (2016)
The molecular geometry of (E)-4-dimethylamino-N′-[(pyridin-2-yl)methylidene- N]benzohydrazide (C15H16N4O) complexed with M2+ (M=Zn, Cu, Ni, Fe, Mn, Ca and Co) ions were calculated, using density functional theory (B3LYP) with 6-31G(d, p) basis set. Vibrational frequencies were computed in order to verify the absence of imaginary vibrational frequencies, fact that confirms the global minimum in geometry optimization. Molecular geometry parameters (bond lengths and angles) for Cu2+ and Zn2+ complexes were compared with crystallographic data previously reported, showing good correlation. Binding energies for all complexes were computed at B3LYP/6-31G++(d, p) level of theory. These calculations indicate that Cu-L is the lowest favorable complex, Cu2+ corresponds to the smallest cation on the present study. In the other hand, Ca-L, one of the less favorable complex, corresponds to the biggest cation analyzed in the present study. Molecular orbital analysis was carried out showing variations in energy differences between HOMO-LUMO values in function of the metallic ion employed.